2009
DOI: 10.1097/01.ogx.0000363241.72396.31
|View full text |Cite
|
Sign up to set email alerts
|

Postlicensure Safety Surveillance for Quadrivalent Human Papillomavirus Recombinant Vaccine

Abstract: The use of synthetic mesh to augment vaginal repair procedures for pelvic organ prolapse has increased in large part because of dissatisfaction with the success rates of traditional colporrhaphy. Its use, however, is controversial. Four randomized controlled studies comparing traditional colporrhaphy with vaginal repair using mesh augmentation had conflicting results. This unblinded, prospective, randomized controlled trial investigated whether mesh augmentation during vaginal repair would reduce the rate of r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
96
2
10

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 76 publications
(111 citation statements)
references
References 14 publications
3
96
2
10
Order By: Relevance
“…Yet, a recent analysis of the quadrivalent vaccine found that the overall rates of adverse events were not greater after HPV vaccination compared with background rates following other types of vaccination. 56 However, a disproportionate number of syncope and venous thrombolic events were observed after HPV vaccination. The venous thrombolic events reported fell within a large time window postvaccination, and 90% of subjects reported having pre-existing risk factors.…”
Section: ■■ Discussion and Limitationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Yet, a recent analysis of the quadrivalent vaccine found that the overall rates of adverse events were not greater after HPV vaccination compared with background rates following other types of vaccination. 56 However, a disproportionate number of syncope and venous thrombolic events were observed after HPV vaccination. The venous thrombolic events reported fell within a large time window postvaccination, and 90% of subjects reported having pre-existing risk factors.…”
Section: ■■ Discussion and Limitationsmentioning
confidence: 99%
“…4 Persistent infection with an oncogenic strain of HPV is the known cause of cervical cancer, 5 the second most common cancer in women worldwide. Of the 40 HPV types that affect the genital area, at least 15 types are known to be oncogenic (types 16,18,31,33,35,39,45,51,52,56,58,59, 68, 73, and 82). 6 The strength of the association between HPV and cervical cancer is at least 10 times greater than the association between smoking and lung cancer.…”
Section: Hpv Vaccination Is An Opportunity For Managed Carementioning
confidence: 99%
See 1 more Smart Citation
“…Data have shown that prophylactic HPV vaccination is generally safe and well tolerated. [32][33][34][35][36][37][38] The median age of sexual debut is in the late teens (15-19 years) in most countries. 39 Virginal adolescents (#15 years old) were not included in HPV vaccine efficacy evaluations because of low HPV exposure and ethical constraints.…”
Section: What This Study Addsmentioning
confidence: 99%
“…2,[7][8][9] Additional objectives of VAERS include monitoring the safety of newly licensed vaccines, 10 assessing potential risk factors for adverse reactions to vaccines, and ultimately improving the safety of vaccines and vaccination practices. VAERS 1-page reporting form collects demographic information about the reporter and the patient as well as a narrative and clinical descriptors regarding AEs.…”
mentioning
confidence: 99%